(untitled) (Journal of Comparative & International Higher Education, 2024)
This study explores the realities and challenges of the internationalization of university administrative staff in Japanese universities empirically because of the increasing globalization of higher education. The functions and roles of administrative staff from the policy perspective with the implementation of mandatory staff development (SD) and reforms to the standards for establishing universities have been considered. This study also attempts to describe the following three aspects: foreign nature of administrative staff, working and/or training overseas experience, and administrative staff’s educational background. The survey data were obtained from available public information on the Japan Society for the Promotion of Science (JSPS) website, particularly the project plans of the Top Global University (TGU) Project, related policy documents. This project includes 37 universities that are conducting world-leading research activities and leading the globalization of Japanese society. In particular, this study focuses 13 Japanese leading universities that are conducting world-level education and research. The results of the data analysis reveal that acquired insights can also become useful inputs for developing university policies in relation to recruitment guidelines and methods and staff training and “human capital development system” in Japanese universities. The conclusion and implications could contribute to the policy making and SD of the internationalizing administrative staff in various countries in terms of foreignness, oversea experience, and educational background.